Discovery and validation of urinary metabotypes for the diagnosis of hepatocellular carcinoma in West Africans - (:unkn) unknown (My University, 2014)
There is no clinically applicable biomarker for surveillance of hepatocellular carcinoma (HCC), because the sensitivity of serum alpha-fetoprotein (AFP) is too low for this purpose. Here, we determined the diagnostic performance of a panel of urinary metabolites of HCC patients from West Africa. Urine samples were collected from Nigerian and Gambian patients recruited on the case-control platform of the Prevention of Liver Fibrosis and Cancer in Africa (PROLIFICA) program. Urinary proton nuclear magnetic resonance ((1) H-NMR) spectroscopy was used to metabolically phenotype 290 subjects: 63 with HCC; 32 with cirrhosis (Cir); 107 with noncirrhotic liver disease (DC); and 88 normal control (NC) healthy volunteers. Urine samples from a further cohort of 463 subjects (141 HCC, 56 Cir, 178 DC, and 88 NC) were analyzed, the results of which validated the initial cohort. The urinary metabotype of patients with HCC was distinct from those with Cir, DC, and NC with areas under the receiver operating characteristic (AUROC) curves of 0.86 (0.78-0.94), 0.93 (0.89-0.97), and 0.89 (0.80-0.98) in the training set and 0.81 (0.73-0.89), 0.96 (0.94-0.99), and 0.90 (0.85-0.96), respectively, in the validation cohort. A urinary metabolite panel, comprising inosine, indole-3-acetate, galactose, and an N-acetylated amino acid (NAA), showed a high sensitivity (86.9% [75.8-94.2]) and specificity (90.3% [74.2-98.0]) in the discrimination of HCC from cirrhosis, a finding that was corroborated in a validation cohort (AUROC: urinary panel = 0.72; AFP = 0.58). Metabolites that were significantly increased in urine of HCC patients, and which correlated with clinical stage of HCC, were NAA, dimethylglycine, 1-methylnicotinamide, methionine, acetylcarnitine, 2-oxoglutarate, choline, and creatine.Conclusion: The urinary metabotyping of this West African cohort identified and validated a metabolite panel that diagnostically outperforms serum AFP.
Keywords: African Research